2001
DOI: 10.1088/0022-3727/34/6/322
|View full text |Cite
|
Sign up to set email alerts
|

Electric discharge in water as a source of UV radiation, ozone and hydrogen peroxide

Abstract: Results are presented from investigations of multispark electric discharge in water excited along multielectrode metal-dielectric systems with gas supply into the interelectrode gaps. The intensity distribution of discharge radiation in the region covering the biologically active soft UV (190⩽λ⩽430 nm) has been determined and the absolute number of quanta in this wavelength interval has been measured. The potentiality of the slipping surface discharge in water for its disinfection is analysed. The energy expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 9 publications
2
86
0
6
Order By: Relevance
“…Measurements performed in our work (see [9]) showed that the radiation spectrum of the multispark discharge in water contains the biologically active component, and the intensity of this component increases substantially as the pulse energy increases.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Measurements performed in our work (see [9]) showed that the radiation spectrum of the multispark discharge in water contains the biologically active component, and the intensity of this component increases substantially as the pulse energy increases.…”
mentioning
confidence: 58%
“…The basic components were a chamber filled with water, a multielectrode system for exciting of slipping surface discharge, and high voltage power supply ( Figure 1). The multielectrode discharge system ( Figure 2) was similar in design to that previously described in [6,8,9]. The discharger consisted of a set of annular electrodes mounted on a dielectric tube surrounding a back-current conductor.…”
Section: Treatment Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Позднее явление электрического пробоя в воде было использовано в технологии электрогидродинамического измельчения [2] и электрогидравлической ударной технологии [3]. Исследования последних лет [4][5][6] по-казали перспективность использования различных конфигураций электрического раз-ряда в жидкости с целью её очистки. Применение плазменных технологий для получе-ния питьевой или даже технической воды связано с явлением электрического разряда в среде с относительно высокой проводимостью.…”
unclassified